The role of solar cooling for nearly zero energy multifamily buildings: Performance analysis across different climates. (July 2022) - Bilardo, Matteo; Ferrara, Maria; Fabrizio, Enrico
Abstract: The building sector has great potential for contributing to the 2030 EU goals of decreasing greenhouse gas emissions and increasing production from renewable sources. This is even more important considering the increasing cooling energy needs. Among the available technologies, solar cooling (SC) represents a good alternative to traditional electric chillers. However, its use in residential buildings is still limited. The aim of this paper is to analyse the potential of solar cooling system in multi-family buildings. A dynamic model of a complete SC system with auxiliary components was developed in TRNSYS to meet the energy demand of a representative nearly zero energy multi-family building in Italy. The performance of different system design alternatives was analysed in eight different climates with special focus on energy storages. The results show how solar cooling should be optimally designed and provide quantification of achievable renewable energy ratios and related costs in the different climates. Highlights: Weather is a determining factor for the design of Solar Cooling (SC) systems. Solar Cooling represent a valuable alternative for nZEB space cooling. Dynamic modelling for optimization of thermal storage is crucial to ensure SC performance. Global design choices should include cost-optimal analysis. A best design scenario has been identified economically and energetically.